PERTEMANAN SEBAYA SEBAGAI ARENA PENDIDIKAN DERADIKALISASI AGAMA - Yusar Yusar (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2015)
This article was an endeavor to describe the arena of the education which aim to de-radicalization, specially among the youth with their peer group. In many cases, the youth is the main target of the radicalism and they were often exploited for the radical movement. In previous researches, the concept of the peer group are rarely considered. Data collected based on several observations in the experiments with the artificial scene of daily life. The youth found their way to show their awareness on the religious radical movement. In some empirical investigations, this article might offers the theoretical framework of peers that may be constructed to study the de-radicalization of religious movement. In the peer life, it was built the force to control the members not to join the radical movement. This article may provide a new approach in terms of  education for de-radicalization of religious movement.